Role of Microfinance in Entrepreneurial Development in Low-Income Areas - Ullah Saif; Ali Mirza Raza; Sidiki Shehla Najeeb (Studies in Business and Economics)
This study examines microfinance’s role in developing entrepreneurship in low-income areas. Entrepreneurship is one of the better ways to eradicate the most critical problems, such as poverty, income inequality, and unemployment. The study uses a paired sample t-test on 200 small entrepreneurs from low-income areas to investigate the difference between before and after availing of a microfinance facility. Furthermore, the microfinance gap is calculated by taking feedback from entrepreneurs before and after getting the financing facility. The microfinance gap is employed to examine whether microfinance plays a role in developing entrepreneurial skills. The results show that the microfinance gap positively contributed to entrepreneurial development. The microfinance facility has proved to be a technique for entrepreneurial development for poor and young unemployed youth. MFIs are considered the best tool to reduce poverty and unemployment and increase entrepreneurial development.